Neurophysiological impact of Vedic chanting on human brainwaves: a spectral electroencephalogram analysis using Gabor transform - Veera Raghava Nalluri; V. J. K. Kishor Sonti (International Journal of Informatics and Communication Technology (IJ-ICT), 2026)
Electroencephalogram (EEG) analysis explores brainwave changes resulting from Vedic chanting (VC) in this experimental study. In this study participants received Vedic recitations from the Rig Veda (RV), Yajur Veda (YV), Sama Veda (SV), and Atharva Veda (AV) which were evaluated through alpha wave (8-12 Hz) measurement to evaluate relaxation response effects known to cause cognitive relaxation and mindfulness. The research captured EEG signals from twenty participants who belonged to four age categories between twenty and fifty years using a fourteen-channel EEG recording system. The signals underwent wavelet-based denoising procedures and Gabor transform (GT) enabled their spectral analysis. Scientists calculated the relaxation factor (RF) for understanding Vedic chant effects on human beings. Vedic Sama provided maximum relaxation effects leading to a 25% RF enhancement whereas YV produced a 20% increase and RV generated 15% enhancement and AV yielded 10% relaxation. The participants between 30 and 45 years old experienced the largest relaxation effects yet their left-brain hemisphere enhanced alpha waves stronger than their right brain region. The statistical methods supported that these results showed meaningful variations. Neural relaxation results from VC practice according to research evidence which shows SV provides the most powerful relaxation effects.